Potential role of sensory bias in plumage pattern evolution: termite-eating and polka-dots in estrildid finches. Issue 1 (2nd January 2021) - Mizuno, Ayumi; Soma, Masayo
Abstract : Conspicuous colour patterns of animals, such as dots or stripes, can function as sexual and/or social signals. Their evolution is often explained by honest indicator mechanisms or the sensory exploitation hypothesis. In birds, however, the latter scenario has been scarcely tested. According to the sensory exploitation hypothesis, prey-like colour patterns can evolve when they contribute to attracting opposite-sex conspecifics by hitchhiking pre-existing sensory systems (sensory bias) that help foraging. Even without cheating scenarios, visual systems can serve as an underlying factor that facilitates the evolution of both foraging behaviours and colour patterns on the body. To test this idea, we examined the relationship between bird plumage patterns and diet using phylogenetic comparative approaches. Specifically, we focused on white polka-dot plumage patterns in estrildid finches and tested whether such patterns evolved for visual sensory systems that help foraging termites and other gregarious whitish small round prey items. Although we predicted that white polka-dots exist in termite-eater species, and that termite-eating evolved before the white polka-dot pattern, ancestral reconstruction did not reveal clear ancestral states for termite-eating. However, the phylogenetic regression model showed that species with conspicuous white polka-dots tended to be termite-eaters. We also found that estrildids with white polka-dots were likely to become termite-eaters, while those without white polka-dots were likely to become non-termite eaters, according to evolutionary transition analysis. These results are in contrast to the prediction of sensory exploitation hypothesis, wherein diet is believed to trigger the evolution of plumage patterns. However, the results presented here suggest that pre-existing sensory bias for white dots may have promoted the evolution of both termite-eating and white polka-dot plumage patterns in estrildids.